Kierkegaard, Lippmann, and the Phantom Public in a Digital Age. - Haman, John P. (Journal of Religious Ethics, 2024)
Søren Kierkegaard and Walter Lippmann wrote in very different times and places but both characterized the public as a "phantom." Importantly, each did so within the context of a broader analysis that linked the press with specific notions about the public and democracy. This paper highlights the specific characteristics of the press that each thinker believed were responsible for the construction of the phantom public and its effects. While taking seriously the differences between Kierkegaard and Lippmann, in both their respective sociopolitical contexts and their formulations of the public and the press, this paper applies their critiques to a vastly different media terrain than either thinker could have envisioned.